Examining the Influence of Mergers and Acquisitions on Financial Performance of the Commercial Banks in Nepal - Amgain, Pushpa Nidhi; Gautam, Rajendra; Parajuli, Sushant (Kanya Journal, 2025)
Mergers and acquisitions (M&A) are strategic actions companies taken to grow their operations, expand their market access, and enhance overall profitability. The purpose of this study is to investigate an impact of mergers and acquisitions on financial performance of the Nepali commercial banks. This research employed a descriptive and casual comparative research design. Three commercial banks—Kumari Bank Limited, Rastriya Banijya Bank Limited, and Nepal Investment Mega Bank Limited—were randomly selected using a lottery method as the sample. The study employed a quantitative approach using annual reports of sampled commercial banks. The published data were taken from the Nepal Rastra Bank supervision report and the sampled commercial bank’s annual report for four years before and after mergers and acquisitions. The data analysis was conducted using mean, standard deviation, correlation, and the paired t-test. Financially, the data shows a decline in return on assets (ROA) and return on equity (ROE) after the merger and acquisitions, The data indicates that ROA and ROE declined after the merger and acquisitions, implications for this study reduced efficiency in asset utilization and overall profitability of sampled commercial banks. However, the performance after the merger become consistent and organized. Consequently, their influence on the financial performance of the sampled commercial banks in Nepal. Future research directions could be examined the influence of mergers and acquisitions(M&A) on financial performance of insurance companies in Nepal.